Convolutional Neural Networks in the Detection of Astronomical Objects from the Messier Catalog - Beluch, Witold; Śliwa, Paweł (Computer Assisted Methods in Engineering and Science, 2023)
This paper explores the application of convolutional neural networks in the field of amateur astronomy. The authors have employed the available astronomical datasets to develop a detector for identifying astronomical objects from the Messier catalog. A concept framework for creating such a detector for astronomical objects using artificial intelligence tools in the form of a detector based on convolutional neural networks is presented. Augmentation and pre-processing procedures have been used to extend the feature distribution in the training set. Examples confirming the effectiveness of the proposed detector of astronomical objects are presented.